1979
DOI: 10.1021/j100475a007
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation temperature effects on hydrogen atom reactions upon radiolysis and photolysis at 4.2 and 77 K of neopentane containing various additives as studied by electron spin resonance

Abstract: 26) P. Neta (private communication) has recorded the ESR spectrum of bpyH2+• at pH 2.3 and 0. The spectrum consists of nine groups of lines of varying Intersltles; the seven central groups are Identical at both pH values while the two extreme groups, although of tow Intensity, appear to be somewhat different at the two pH values which could Indicate the onset of a pKa at the higher acidity. ( 27) M. Simic and E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…However, for the Kr (mp 116 K) matrices it was difficult to prepare homogeneous samples at 77 K, and the better results were obtained from the samples frozen at 4.2 K. In addition, to ensure good thermal conduction and equilibrium during the thermal annealing at elevated temperatures and the subsequent ESR measurements at 4.2 K, we filled the sample tubes with helium to ~0.5 atm at 77 K (or 4.2 K) before sealing them off. 7 In checking the undesirable effects of helium gas in the sample tubes, we further confirmed that the results are the same as those obtained from the sample in an evacuated tube. The sample tubes used were of 4-mm diameter, and essentially the same results were also obtained from the sample tubes of 2-mm diameter.…”
Section: Methodssupporting
confidence: 76%
“…However, for the Kr (mp 116 K) matrices it was difficult to prepare homogeneous samples at 77 K, and the better results were obtained from the samples frozen at 4.2 K. In addition, to ensure good thermal conduction and equilibrium during the thermal annealing at elevated temperatures and the subsequent ESR measurements at 4.2 K, we filled the sample tubes with helium to ~0.5 atm at 77 K (or 4.2 K) before sealing them off. 7 In checking the undesirable effects of helium gas in the sample tubes, we further confirmed that the results are the same as those obtained from the sample in an evacuated tube. The sample tubes used were of 4-mm diameter, and essentially the same results were also obtained from the sample tubes of 2-mm diameter.…”
Section: Methodssupporting
confidence: 76%
“…The reactions of H atoms at cryogenic temperatures have been studied extensively, and it is known that hydrogen addition to unsaturated hydrocarbons occurs at 77 K or below. ,, At cryogenic temperatures the H addition reaction is controlled primarily by H atom diffusion. Diffusion control of this reaction is in accordance with (1) negligible activation energies in some cases (Table ) and (2) the occurrence of quantum mechanical tunneling of H atoms when the reaction is not barrier-free.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned, however, that Iwasaki, Toriyama and co-workers [44][45][46] ascribed the selective formation of protiated radicals in mixed crystals to reactions of thermal D-atoms rather than to exciton migration. The observed suppression of energy transfer at 4 K was considered to be the main evidence against the exciton mechanism (compare with Section 2.3.1).…”
Section: Events Leading To Radical Formationmentioning
confidence: 99%
“…and R2 H + I~I ~ 1~2 +H2 (2) were considered by Iwasaki and co-workers [44][45][46]48] to be the main mechanism for radical pair production (see Section 2.3.1) and for radical site migration (see Section 2.5), as well as for the preferential formation of protiated radicals in mixed crystals, mentioned above. The fact that no trapped H-atoms were detected in alkanes at 4.2 K [49] was attributed to their rapid tunnel abstraction reaction with surrounding molecules.…”
Section: R~h-~ R~ + Fl (1)mentioning
confidence: 99%